Inhaled RNA Therapeutics for Obstructive Airway Diseases: Recent Advances and Future Prospects - You Xu; Aneesh Thakur; Yibang Zhang; Camilla Foged (MDPI AG, 2021)
Obstructive airway diseases, e.g., chronic obstructive pulmonary disease (COPD) and asthma, represent leading causes of morbidity and mortality worldwide. However, the efficacy of currently available inhaled therapeutics is not sufficient for arresting disease progression and decreasing mortality, hence providing an urgent need for development of novel therapeutics. Local delivery to the airways via inhalation is promising for novel drugs, because it allows for delivery directly to the target site of action and minimizes systemic drug exposure. In addition, novel drug modalities like RNA therapeutics provide entirely new opportunities for highly specific treatment of airway diseases. Here, we review state of the art of conventional inhaled drugs used for the treatment of COPD and asthma with focus on quality attributes of inhaled medicines, and we outline the therapeutic potential and safety of novel drugs. Subsequently, we present recent advances in manufacturing of thermostable solid dosage forms for pulmonary administration, important quality attributes of inhalable dry powder formulations, and obstacles for the translation of inhalable solid dosage forms to the clinic. Delivery challenges for inhaled RNA therapeutics and delivery technologies used to overcome them are also discussed. Finally, we present future prospects of novel inhaled RNA-based therapeutics for treatment of obstructive airways diseases, and highlight major knowledge gaps, which require further investigation to advance RNA-based medicine towards the bedside.